2023
DOI: 10.1021/acsmedchemlett.3c00019
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Artesunic Acid–Coumarin Hybrids as Potential Antimelanoma Agents

Abstract: Current therapy against melanoma relies on surgical treatment or, in alternative, on conventional drug therapy. Often these therapeutic agents are ineffective due to the development of resistance phenomena. For this purpose, chemical hybridization emerged as an effective strategy to overcome the development of drug resistance. In this study, a series of molecular hybrids were synthesized combining the sesquiterpene artesunic acid with a panel of phytochemical coumarins. Cytotoxicity, antimelanoma effect, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…We selected bioactive coumarins as prominent and suitable pharmacophores. While few examples of anticancer artemisinin-coumarin hybrids are known, 30–32 no examples of antimalarial artemisinin-coumarin hybrid compounds and their in vitro / in vivo analyses and mode of action studies have been reported to date. Coumarin derivatives e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We selected bioactive coumarins as prominent and suitable pharmacophores. While few examples of anticancer artemisinin-coumarin hybrids are known, 30–32 no examples of antimalarial artemisinin-coumarin hybrid compounds and their in vitro / in vivo analyses and mode of action studies have been reported to date. Coumarin derivatives e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Then, they were incubated for 24 h. The Cell Counting Kit-8 solution (10 L) was added to each well, and the mixture was incubated for an additional 3 h at C. The absorbance of each well at 450 nm was measured using a VICTOR Nivo Multimodr Plate Reader. The 50% inhibitory concentrations ( ) of imatinib, nilotinib, AT-9283, and ZM-306416 were calculated using GraphPad Prism software (Version 9.0) [ 47 ].…”
Section: Materials and Methodsmentioning
confidence: 99%